Respuesta :

First note the domain of the expressions on either side of the equation,

[tex]\sqrt{x^2 + 4x + 7} = \sqrt{x^2 - 2x + 4}[/tex]

x is defined only for x ≥ 0, so we need to have

[tex]x^2 + 4x + 7 \ge 0 \\\\ (x^2+4x+4) + 3 \ge 0 \\\\ (x+2)^2 \ge -3[/tex]

and

[tex]x^2 - 2x + 4 \ge 0 \\\\ (x^2 - 2x + 1) + 3 \ge 0 \\\\ (x-1)^2 \ge -3[/tex]

but x ² ≥ 0 for all real x, so both conditions will always be satisfied.

Back to the equation - take the square of both sides and solve for x :

[tex]x^2 + 4x + 7 = x^2 - 2x + 4 \\\\ 4x + 7 = -2x + 4 \\\\ 6x = -3 \\\\ \boxed{x=-\dfrac12}[/tex]

ACCESS MORE